Nanoparticle-induced unusual melting and solidification behaviours of metals - Chao Ma (Nature Portfolio, 2017)
A material with a deep melted zone (MZ) but small heat-affected zone (HAZ) is ideal for manufacturing, but improving one zone comes at the expense of the other. Here, the authors resolve this contradiction in metals by adding nanoparticles, which change the metals’ properties in such a way that both expands MZ and minimizes HAZ.